Application of SELDI-TOF mass spectrometry in clinical evaluation of thrombotic thrombocytopenic purpura. Issue 5 (2006) - Wu Wu, Haifeng M. Haifeng M.; Cataland Cataland, Spero R. Spero R.; Bissell Bissell, Michael Michael; Jin Jin, Ming Ming
Abstract : Surface Enhanced Laser Desorption/Ionization Time Of Flight (SELDI-TOF) mass spectrometry is characterized by integration of mass spectrometry with surface chemistry, which gives rise to rapid purification and subsequent determination of protein/peptide analytes. There are several surface matrices, named proteinChips, available for analyzing a particular analyte or a subset of biomolecules in biological samples. Each proteinChip has a unique surface property suitable for fractionation of a specific group of molecules. This article demonstrates the application of SELDI-TOF for the analysis of a cleaved peptide ( Mr 7739 daltons) from von Willebrand Factor by a metalloproteinase, ADAMTS13. Deficiency of ADAMTS13 is a known primary risk factor for the devastating hematological disorder, Thrombotic thrombocytopenic purpura (TTP). Rapid determination of ADAMTS13 activity helps clinicians tremendously in making the correct diagnosis and initiating timely therapy. Most patients with TTP are acquired cases who exhibit a production of autoimmune antibodies against ADAMTS13 protease. TTP's clinical course is critically controlled by the autoantibody's ability to inhibit ADAMTS13 function. Thus, a second SELDI-TOF based test has been devised to measure ADAMTS13 autoantibody activity for the evaluation of TTP disease activity. In conclusion, the unique features of SELDI-TOF which allow for the examination of the role of key proteases in disease processes have opened up new doors for the clinical application of mass spectrometer based techniques.